If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + -7) = 3(8x + 5) Reorder the terms: 6(-7 + 4x) = 3(8x + 5) (-7 * 6 + 4x * 6) = 3(8x + 5) (-42 + 24x) = 3(8x + 5) Reorder the terms: -42 + 24x = 3(5 + 8x) -42 + 24x = (5 * 3 + 8x * 3) -42 + 24x = (15 + 24x) Add '-24x' to each side of the equation. -42 + 24x + -24x = 15 + 24x + -24x Combine like terms: 24x + -24x = 0 -42 + 0 = 15 + 24x + -24x -42 = 15 + 24x + -24x Combine like terms: 24x + -24x = 0 -42 = 15 + 0 -42 = 15 Solving -42 = 15 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -29=x-47 | | 3(b+2)=9b | | 20x-42=24x+15 | | 9(n-6)=6n | | n(n-6)=9 | | 14z-4y= | | 3x+5-6x=2+8x-6 | | nn-6=9 | | 19x+3=5-6x | | a-45=12 | | -2p+7=6-(10p+4) | | 3+b=.5 | | 40x+2(1.5)=430 | | x+100+500=x | | f=-2x^2+9x+7 | | 5=ln(x+8) | | 0.45+.05(16-x)=.10(24) | | 40=250*r | | 3x-7+2x+5=108 | | 40=250xr | | x^2+2x-4= | | x=-2x^2+9x+7 | | 7-n=19 | | n+7=19 | | 9x^2+24x+36=0 | | 7+19=n | | y=20x^2+5x-6 | | 8y+8=14 | | 0.36(12)+0.04x=0.12(6+x) | | 10x-2(x-4)=8x+2 | | 6(4x-4)=2(12x+3) | | -4x^3-9x+2=0 |